Metamorphosis of Learning Ecosystems in Response to The Fourth Industrial Revolution's (4IR) - Loso Judijanto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This review provides a comprehensive overview of the Fourth Industrial Revolution (4IR) and its educational impact. It focuses on the accelerated pace of technological advancements and the urgent need to understand how these changes affect educational systems. The research, which includes empirical studies, theoretical frameworks, and policy literature, employs a thematic analysis to identify key trends and themes using secondary data like books, research findings, and scientific journals related to 4IR. Key findings highlight the increasing demands for new skills in the workforce, ethical considerations, and the necessity for an interdisciplinary approach in education. The study underscores the transformation of education in the wake of 4IR's influence, particularly in automation and artificial intelligence (AI). It emphasizes the importance of adapting educational paradigms to address the challenges and opportunities presented by these technological advancements. The study's major implication is the need for a fundamental shift in learning ecosystems to align with the transformative power of 4IR. This involves adapting to significant changes in the educational landscape, which are necessary to facilitate user ease. Integrating modern intelligent technologies has fundamentally altered production and global supply networks, leading to increased automation, enhanced communication, and smart machines. This transformation underscores the need for educational systems to evolve and prepare for these ongoing changes.